Physical activity and hormonal cycles in women: the need for a more active life in the post-pandemic era. - Mattioli, Anna Vittoria; Coppi, Francesca (Progress in Nutrition, 2022)
The present letter to the editor comments on the manuscript “Gonzalo Algul S, Alp B, Ozcelik O. Menstrual cycle and Exercise. Progr Nutr [Internet]. 2022 Mar. 28 [cited 2022 Apr. 3];24(1):e2022021. Available from: https://www.mattioli1885journals.com/index.php/progressinnutrition/article/view/11435